Strengthening the Protection of Children's Rights for Family Empowerment and Welfare Cadres in Giripurwo Village, Girimulyo, Kulonprogo, DIY: Penguatan Perlindungan Hak Hak Anak Pada Kader PKK Kalurahan Giripurwo, Girimulyo, Kulonprogo, DIY - Cunduk Wasiati; Chrisjanto, Edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Cases of child abuse in the Special Region of Yogyakarta increased in the first semester of 2024 compared to last year. From January to June 2023 there were 222 cases, while data from January to June 2024 showed 226 cases. The total of 226 cases of child abuse is an accumulation of four districts and one city of Yogyakarta. Kulon Progo Regency had 16 cases, Bantul 41 cases, Gunungkidul 31 cases, Sleman 73 cases and the city of Yogyakarta Sabangak 65 cases. Based on these data, Sleman Regency is in the highest position, namely 73 cases. The age of children who experienced the most cases of violence was in the age range of 11-17 years, as many as 164 cases. The next data is written 0-5 years 14 cases, 6-10 years 48 cases. The cases of violence are divided into two, namely violence against children and violence against women. Data from 2024, there were 352 cases of violence against women. So if totaled there are 578 cases of violence in the first semester of 2024. Psychological violence as much as 209, physical violence 201, sexual violence 145, neglect 20 exploitation three cases. By looking at the regulation of children's rights in several regulations, children should have the right to get their rights. Based on the data above, it turns out that there are still many children in DIY who have not received recognition, fulfillment and protection of their rights. The results of the legal counseling activity, namely when it was held, several participants from the PKK Cadre provided very good feedback by asking questions and exchanging experiences related to the task of providing services and assistance to the community that they had experienced. In addition, families who have children gain knowledge about the rights of their children which are guaranteed by law. Kata Kunci: 1. Perlindungan;2. Hak Anak; 3. Kader .